Uma proposta de ensino envolvendo geometria fractal para o estudo de semelhança de figuras planas - Gomes, Antônio do Nascimento (Universidade Federal de São Carlos, 2010)
The main objective of this research is develop a teaching material by exploring the Fractal Geometry helps students and teachers in teaching-learning process the concepts of Similarity of Figures, among others, present in the curriculum of 8th grade of Elementary School. In this sense, we work with Activities Sheets that connect content that are part of the curriculum with the Fractal Geometry, because it looks playful and investigative. From activities undertaken and the testimony of interviewees we note the great commitment and interest from them. We also intend to show how was the process of developing this material by students and their acceptability in terms of a Research on Their Own Professional Practice (PONTE, 2002). We still investigated the Euclidean Geometry, from which much of the school geometry comes and the Fractal Geometry systematized by Mandelbrot in the last decades of the twentieth century, considering the possibility of its presence in the curriculum of Basic Education, particularly in São Paulo s Curriculum Proposal.
Keywords: Matemática - estudo e ensino; Geometria fractal; Motivação na educação; Educação - proposta curricular; Teaching of mathematics; Fractal geometry; Motivation; Curriculum proposal; CIENCIAS EXATAS E DA TERRA::MATEMATICA